Arctic Corridors and Northern Voices: governing marine transportation in the Canadian Arctic (Resolute, Nunavut community report) - Carter, Natalie; Dawson, Jackie; Cook, Alison (Université d'Ottawa | University of Ottawa, 2019)
Ship traffic in the Canadian Arctic nearly tripled between 1990 and 2015. The Government of Canada is developing a network of low-impact marine transportation corridors in the Arctic that encourages marine transportation traffic to use routes that pose less risk and minimize the impact on communities and the environment. The Low Impact Shipping Corridors will be a framework to guide future federal investments to support marine navigation safety in the North, including improved charting and increased hydrography, in partnership with Northerners. The corridors initiative is co-led by the Canadian Coast Guard, Transport Canada, and Canadian Hydrographic Service. Key considerations in the current prioritization of the Low Impact Shipping Corridors include identification of Inuit and Northerners’ perspectives on 1) the potential impact of marine vessels on marine areas used for cultural and livelihood activities, and on community members; and 2) potential management strategies for the corridors. This report reflects opinions gathered through participatory mapping, focus group discussions, and interviews with Resolute community members who were identified by local organizations as key knowledge holders. This report was validated by the research participants.
Keywords: Low impact shipping corridors; Marine transportation governance; Culturally significant marine areas; Culturally significant marine areas; Arctic shipping impacts